Implementasi Rukiah dengan Selang di Polewali Mandar: Suatu Kajian Ihya Al-Sunnah - Nur Muthmainnah Mudir (Ihyaussunnah : Journal of Ulumul Hadith and Living Sunnah, 2024)
The research discusses the implementation of rukiah with a hose in Lemo Baru Hamlet, Kuajang Village, Binuang District, Polewali Mandar Regency which will be seen in the review of iḥyā as-sunnah by knowing the problems, namely: 1) What is the quality of the hadith about rukiah? 2) How is the understanding of hadith about rukiah with a hose in Lemo Baru Hamlet, Kuajang Village? 3) How is the implementation of sunnah values on rukiah with a hose in Lemo Baru Hamlet, Kuajang Village? This type of research is classified as qualitative based on descriptive field research with the research approach used as sociological approach and phenomenology. The data sources of this research are the Rukiah, Rukiah Patients, Religious Leaders, Traditional Leaders, Village Heads, and the Community. Furthermore, the data collection methods used are observation, interviews, documentation, and reference searches. Then, data processing and analysis techniques are carried out through two processing methods, namely the deductive method and the comparative method, and three stages of data analysis, namely: data presentation, data reduction, and verification then concluding. The results showed that rukiah with a hose in Lemo Baru Hamlet, Kuajang Village with the study of iḥyā as-sunnah. In the aspect of the quality of the hadith which is the object of research, it is considered as a hadith that can be used as a basis for footing and is supported by the involvement of Muslims in the line of transmission. The understanding of the community regarding this matter shows that the hadith contains legal evidence for the permissibility of doing rukiah and is also an effort to revive the hadith or sunnah of the Prophet Muhammad PBUH. The implementation of sunnah values in rukiah with a hose in Lemo Baru Hamlet, Kuajang Village is the legal value of the permissibility of doing rukiah and is an effort to revive the sunnah of the Prophet Muhammad PBUH, there is the value of reading the Qur'an, there is the value of helping, and there is the value of da'wah. This research provides an in-depth understanding of the practice of rukiah with a hose in Lemo Baru Hamlet and its relation to the concept of Iḥyā Sunnah in Islamic tradition. The research findings can be a study material for academics, therapists, and observers of Islamic traditions to understand the various implementations of spiritual practices that develop in the community.